Energi Alternatif Melalui Getaran Beban Mekanis - Dimas Ramadhan Putra; Jhav Sund Oktoricoento; Sahrudin Sahrudin; Mohammad Mujirudin; Harry Ramza; Oktarina Heriyani; Akhiruddin Maddu (Prosiding Seminar Nasional Teknoka, 2018)
Electricity needs increase over time. Electricity is a very important requirement that is used to facilitate human life, for example for lighting at night, running household appliances and for various other human works. This research was carried out by making a small-scale prototype model which was measured by Digital Multimeter DT830B series.The data obtained from the testing of piezoelectric sensors showed that when compiled in series, the highest output power was 19.4888 μW with a maximum load of 186 kg, while for the preparation of sensors in parallel the resulting power reached 61.5043 μW from a load of 186 kg as an indication of the mechanical load vibration provided.